Inovasi Strategi Pendampingan Humanis pada Program 'Yaumul Arabi' Berbasis Metode Imersif bagi Siswa Non-Asrama - Maula Nada Munthe; Teguh Wahyu Wicaksono (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
The establishment of conventional language environments (biah lughawiyyah) often stagnates and triggers language anxiety among students due to repressive monitoring systems, such as spying (jasus) and rigid sanctions. This study aims to examine the reconstruction of the Yaumul Arabi program through innovative humanistic mentoring strategies and to measure its effectiveness in boosting students' confidence within non-boarding educational institutions. The research method employs a literature review integrated with a qualitative reflective approach (autoethnography). The results indicate that the humanistic approach effectively lowers learners' affective filters through three main stimulants: casual conversation (al-hiwar al-bashiith) to trigger confidence, the integration of behaviorist theory-based language games (al-ab al-lughawiyyah) to enrich vocabulary effortlessly, and the optimization of peer tutoring to break down psychological formalities. Despite the constraints of limited face-to-face interaction in non-boarding settings, this innovation can be modernly implemented through a hybrid approach utilizing digital ecosystems. This study concludes that a pressure-free, language-friendly atmosphere stimulates intrinsic motivation and speaking fluency (maharah kalam). Future researchers are encouraged to conduct true experimental studies to test the empirical effectiveness of this formula on a broader scale.